Analysis of 35 cases of Xanthogranulomatous pyelonephritis. Issue 3 (25th March 2014) - Addison, Ben; Zargar, Homayoun; Lilic, Nikola; Merrilees, David; Rice, Michael
Abstract Background To retrospectively determine key demographic and clinical features of 35 patients with Xanthogranulomatous pyelonephritis (XGP) in a New Zealand setting and to compare it with the existing literature. Methods A retrospective review of patients having a confirmed diagnosis of XGP on histopathology examination was performed. Key clinical and demographic features were analysed and compared with the published literature. Results XGP was diagnosed in 35 patients over a 12‐year (2001–2013) period in Auckland Public Hospital. Ninety‐one percent of the patients were female. The population had significantly higher numbers of Maori and Pacific Island patients compared with the general population (74%). Staghorn calculi were the most common cause (51.4%) with obstructing ureteric calculi as the next most common (22.9%) cause. Twenty percent of cases were not thought to be XGP prior to nephrectomy (suspicious renal mass). Thirteen (38%) patients suffered serious complications post‐operatively (Clavien 3–5). Conclusion XGP is a rare chronic inflammatory condition that appears to be overrepresented by Maori and Pacific islanders in our cohort when compared with the overall patient pool. Surgical treatment is associated with significant morbidity but remains the only definitive option. Obesity and other conditions associated with metabolic syndrome may coexist at the time of presentation and may be contributing factors to the development of XGP and poor outcomes associated with it.